Technical Advancements Toward RIS-Assisted NTN-Based THz Communication for 6G and Beyond - Oluwatosin Ahmed Amodu; Rosdiadee Nordin; Nor Fadzilah Abdullah; Sherif Adeshina Busari; Asma' Abu-Samah; Ifiok Otung; Muhammad Ali; Mehran Behjati (IEEE Access)
The world is experiencing an explosion in demand for ultra-high data rates with far greater expectations in the next few years. These expectations, given the bandwidth-demanding applications such as augmented and virtual reality and other beyond-5G applications, motivate the exploration of higher-frequency communication in the terahertz (THz) bands. However, THz communication is faced with many technical challenges, primarily due to the high susceptibility to blockages that limit its applications. Here, reconfigurable intelligent surfaces (RIS) provide alternative paths to circumvent such blockage effects and ensure reliable, spectral, and energy-efficient communication, thus advancing the THz-RIS technology concept. However, the ambitious targets of ubiquitous and global connectivity can only be satisfied by many technologies extending to multiple domains, from terrestrial networks to non-terrestrial network (NTN) domains. The use of airborne and spaceborne networks is considered a potential solution for addressing these challenges due to their dynamism, coverage, and ability to leverage their altitude for achieving line-of-sight communication for enhanced signal quality and network performance. Therefore, unmanned aerial vehicles, high-altitude platform stations, and satellites are poised to use flying THz-based RISs to improve air-to-ground and space-to-ground communication reliability while exploiting novel RIS architectures, techniques and enablers to address the issues regarding the propagation conditions, hardware limitations, network complexity and system performance. The aim in this paper is to present the discussion and a survey on the technical advances on THz-RIS NTNs, in addition to outlining potential applications, architectural variants, influencing properties, as well as its prospects, associated challenges, open issues and future directions towards high-data rate THz-RIS NTN communication for 6G and beyond.